2019
DOI: 10.1371/journal.pone.0213920
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the barriers and factors to HIV testing intention of women engaging in compensated dating in Hong Kong: The application of the extended Theory of Planned Behavior

Abstract: Background Women engaging in compensated dating is one of the at risk group of HIV infection due to multiple sexual partnerships and risky sexual practices. The present study examined the prevalence of HIV testing behavior and intention, and identified factors associated with HIV testing intention among women engaging in compensated dating in Hong Kong. Factors from the Theory of Planned Behaviors and the role of various types of barriers to HIV testing were also explored. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…Consistent with previous research [ 36 , 37 ], there was an association between past HIV testing experience and intention to test, indicating that efforts to get people tested for the first time would be a significant investment HIV testing attitudes and behavior in the future. It is worth noting that there was no association between awareness of free anonymous testing for Thai nationals with HIV testing experience or intention to test; only less than half of our respondents were aware of their eligibility to receive free and anonymous HIV testing.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous research [ 36 , 37 ], there was an association between past HIV testing experience and intention to test, indicating that efforts to get people tested for the first time would be a significant investment HIV testing attitudes and behavior in the future. It is worth noting that there was no association between awareness of free anonymous testing for Thai nationals with HIV testing experience or intention to test; only less than half of our respondents were aware of their eligibility to receive free and anonymous HIV testing.…”
Section: Discussionsupporting
confidence: 88%
“…The attitude was significant to adherence to quarantine protocols based on the study's results. This validates the existing literature that attitude is a predictor of actual behavior (Agarwal, 2014;Mo et al, 2019;Omodior et al, 2015;Schmid et al, 2017;Yang, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The results show that attitude was significant to adherence to quarantine protocols. This supports existing literature that attitude predicts actual behavior (Agarwal, 2014;Mo et al, 2019;Omodior et al, 2015;Schmid et al, 2017;Yang, 2015). The relationships between attitude and social media were statistically significant.…”
Section: Indirect Effect Pathssupporting
confidence: 89%
See 1 more Smart Citation
“…Another study in Ethiopia among health professionals (male and female) found that subjective norm and attitude were the most important contributors to the variance in the intention to test for HIV (Abamecha et al, 2013). In a more recent study among women engaging in compensated dating in Hong Kong, the intention to undergo HIV testing was significantly predicted by attitudes, subjective norms, perceived behavioural control, ever having been tested for HIV and perceived discrimination from health care workers, explaining 42% of the variance in intention (Mo et al, 2019). The overall variance explained by these studies ranges between 9.2% and 42%.…”
Section: Introductionmentioning
confidence: 97%